The role of IL-23/IL-17 axis in ischemic stroke from the perspective of gut-brain axis. (15th June 2023) - Jiang, Yang; Dai, Yajie; Liu, Zhenquan; Liao, Yan; Sun, Shuyong; Kong, Xianghe; Hu, Jingjing; Tang, Yibo
Abstract: Bidirectional communication between central nervous system (CNS) and intestine is mediated by nerve, endocrine, immune and other pathways in gut–brain axis. Many diseases of CNS disturb the homeostasis of intestine and gut microbiota. Similarly, the dysbiosis of intestinal and gut microbiota also promotes the progression and deterioration of CNS diseases. IL-23/IL-17 axis is an important inflammatory axis which is widely involved in CNS diseases such as experimental autoimmune encephalomyelitis (EAE), multiple sclerosis (MS), and ischemic stroke (IS). Attributing to the long anatomically distances between ischemic brain and gut, previous studies on IL-23/IL-17 axis in IS are rarely focused on intestinal tissues. However, recent studies have found that IL-17 + T cells in CNS mainly originate from intestine. The activation and migration of IL-17 + T cells to CNS is likely to be affected by the altered intestinal homeostasis. These studies promoted the attention of IL-23/IL-17 axis and gut-brain axis. IS is difficult to treat because of its extremely complex pathological mechanism. This review mainly discusses the relationship between IL-23/IL-17 axis and IS from the perspective of gut-brain axis. By analyzing the immune pathways in gut-brain axis, the activation of IL-23/IL-17 axis, the roles of IL-23/IL-17 axis in gut, CNS and other systems after stoke, this review is expected to provide new enlightenments for the treatment strategies of IS. This article is part of the Special Issue on "Microbiome & the Brain: Mechanisms & Maladies". Highlights: IL-23/IL-17 (IL-23, IL-17, IL-17 + T cells) axis plays an important role in neuroinflammation after stroke. After stroke, the intestinal barrier is damaged, and then the translocated microflora activates intestinal immunity. There is growing evidence that IL-17 + T cells are activated in the intestine and then migrate to CNS. Translocated microflora and IL-17 + T cells may cause multiple-organ inflammatory injury.